Tourism through troubled times : challenges and opportunities of the tourism industry in 21st century - Korstanje, Maximiliano E.; Séraphin, Hugues; Maingi, Shem Wambugu (Tourism security-safety and post conflict destinations., 2022)
Tourism Through Troubled Times explores the unparalleled crisis within the current global tourism industry, which includes not only a wide range of risks that threaten economic activity but also a wider and deeper epistemological crisis. Divided into four sections covering risk perception, tourism in crisis, new forms of tourism and the future of tourism in a fractured world, this edited collection examines issues including the impacts of the climate crisis on tourism, post-disaster marketing and management, use of robotics tourism, dark tourism, virtual tourism, over-tourism and tourism-phobia. The editors present perspectives from a range of scholarly voices throughout a diverse array of chapters, offering a multidisciplinary view on tourism's recovery and possible future. Tourism Through Troubled Times is an illuminating read for all scholars of Tourism Studies, Hospitality Management, and the Sociology of Tourism, as well as practitioners and managers within the hospitality sector, and gives clear insights into the industry's next steps forward.